APLIKASI ePOSYANDU KESEHATAN IBU DAN ANAK DI KECAMATAN KEMPAS JAYA - Dwi Yuli Prasetyo; Fitri Yunita; Ricky Setiawan (JURNAL PERANGKAT LUNAK, 2021)
Posyandu Srikandi II is a health service unit tasked with providing maternal and child health services (KIA) in the area of ??RT 05 d RW 09 Kempas Jaya Village, Kempas District. Currently, the data management process at the Srikandi II Posyandu is still done manually by recording data into a register format book. This method is considered inefficient because it causes difficulties in the data management process of Posyandu Srikandi II. To overcome these problems, the authors intend to develop a web-based Posyandu information system. Data was collected by means of observation and interviews. The system development method used is the Unified Modeling Language (UML). The tools used in system analysis and design are Use Case Diagrams, Activity Diagrams, Squance Diagrams, and Class Diagrams. From the results of testing and evaluation interviews conducted with the Head of Posyandu Srikandi II, it was concluded that this eposyandu application could facilitate the processing, searching, and reporting of data on Posyandu Srikandi II activities. In the next development, it is hoped that this posyandu information system will be equipped with a KMS band chart feature to monitor the development of children's weight.